Improving Long Jump Squat Style Using Used Tyres - Hanafi, Suriah (Sains Global Institut, Indonesia, 2024)
This research is a classroom action research that aims to determine whether the use of used tyres can improve results and improve the push-off aspect in the long jump. The population is all fifth-grade students at SD Negeri ½ Pangkajene, Pangkep Regency, totalling 25 students. The determination of the sampling technique is by simple random sampling. The data analysis technique used is descriptive analysis. The results of the study showed that there was a significant increase in the results of the squat style long jump ability of fifth-grade students of SD Negeri ½ Pangkajene, where in cycle I the percentage of student graduation was 47.39% and increased in cycle II with a percentage of graduation of 84.21%.